فہم حدیث سے متعلق محدثین کا منہج ومعیار اور امتیازی خصوصیات (تحقیقی جائزہ): The Approach, Quality, and Distinguishing Characteristics of Muhadditheen related to the Understanding of Hadith (Research Review) - Yousaf , Muhammad; Deen , Salah ud; Haroon Agha, Syed Muhammad (Journal of Quranic and Social Studies, 2023)
Islam is a universal religion in which is guidance and direction for human beings till the Day of judgment and it is the quality of Islam that it contains the solution of all kinds of problems of mankind till the Day of judgment.There is no doubt that the text of the Quran and Sunnah are based on comprehensiveness which has that status and considered the principle and law in Islam.But whenever a new issue occurred in human life, the people of wisdom and knowledge has found the solution by looking into texts of Quran and Sunnah in the light of certain rules and regulations. This religious endeavour has been termed in Islamic literature as inference, effort or jurisprudence in Islamic literature.Although the term jurisprudence (Fiqah)was generally used for understanding religion in the early days of Islam, when the scientific arts developed. Hadith and jurisprudence (Fiqah)became two separate terms, so the people who used to work in the field of Hadith became known as muhaddithin (Muhaddiseen)and the people who used to provide their services in the field of Fiqah became known jurists (Fiqah).Now the method of the two have Ibid became different in the inference from the shariah texts.The following article discuss the principles of the muhaddihin and the jurists on the basis of which they derived rulings from Hadiths of the prophet and then at end a comparative analysis of the two presented.The second chapter deals with the different periods of jurisprudence (Fiqah)and the general inference of the four school of thoughts. The third chapter deals with the methodology and standards of Muhaddithin and jurists regarding the understanding of Hadith, while the fourth and final chapter provide comparative study of the methodology of Muddihin and four jurists (Fuqaha).